Physical and chemical properties of some 4-amino-5-(furan-2-, 2-metylfuran-3-yl)-1,2,4-triazole-3-thiol alkyl derivatives - D. M. Danilchenko; V. V. Parchenko; O. I. Panasenko; Ye. G. Knysh (Zaporozhye State Medical University, 2016)
Publications of domestic and foreign scientists in the last ten years clearly show that the search for new molecules among 1,2,4-triazole furan derivatives has not only theoretical interest in the study of physical and chemical properties of compounds, but also has a practical significance on the implementation of the most active agents in various spheres of human activity. The most striking example is the registration of new domestic veterinary drug «Tryfuzol 1% solution for injections» (registration certificate AB-05486-01-14 from 01.10.2014). Active substance of the «Tryfuzol» is a water-soluble substance, which is furan derivative of 1,2,4-triazole-3-thione according to the chemical formula. Aim. Further research of reactions which are related to the study of physical and chemical properties of new 1,2,4-triazole-3-thione derivatives with heterocyclic furan system fragments, is an important task in the search for new biologically active compounds needed for the potential drugs creation. Methods and results. For the first time we have synthesized the number of 4-amino-5-(furan-2, 2-metylfuran-3-yl)-1,2,4-triazole-3-thiol alkyl derivatives. As alkylating agents we have used appropriate bromalkans. Conclusions. The structure of the synthesized compounds has been confirmed by complex physical and chemical analysis methods (elemental analysis, NMR spectroscopy, chromatography-mass spectrometry), and their individuality has been confirmed chromatographically.